Death in Irish accents - Murphy, C. E. (Catie E.) (Murphy, C. E. (Catie E.). Dublin driver mystery., 2023)
Unable to stay out of trouble for too long, Dublin limo driver Megan Malone helps her latest client, a world-renowned romance novelist, look into the death of her protégé, leading her to the victim's writing group and to a killer who wants to write her out of the story--permanently.